REALISASI PEMENTINGAN INFORMASI PADA KALIMAT DALAM BAHASA INGGRIS - Ikmi Nur Oktavianti (Adabiyyāt: Jurnal Bahasa dan Sastra, 2014)
To achieve the goal of using language, the speaker of a language is structuring the linguistic construction as effective as possible. Moreover, he is able to modify the linguistic construction based on the prominence of the information. By so doing, language will meet its function, serving as the tool of delivering message to the interlocutor. However, there are many ways to mark the important information, such as supra-segmental, morphological, and syntactic ways. Syntactic marking of information packaging is called syntactic choice. Thus, this paper aims at describing the ways to package important information in English as one of widely spoken languages worldwide. This study belongs to descriptive qualitative study. The data were taken from realiable sources, written or spoken by native speakers. From the analysis, it is evident that English has several ways of structuring prominent information and resulting in some noncanonical constructions, namely topicalization, dislocation, cleft, existential, and so forth.